Agricultural Enterprisesdevelopment to Enable Perfect Utilization of Available Space in Development - Qodirovich, Karimov Erkin; Obidovich, Ahmadov Behzod; Mamadaliyech, Shovkiev Ahad; o’g’li, Sherqulov Sherzod Jamshid (European Journal of Life Safety and Stability (2660-9630), 2023)
this article focuses on the development of agricultural enterprises in our country, the attention paid to them by the state, the role and importance of multi-sectoral farms in agriculture, and the prospects of agroclusters.